A Lean Thinking Approach for Sustainable Improvement of Outpatient Pharmaceutical Service Processes In Hospital “X” - Elsyahrani Rafika Intan; Chitra Astari; Jasril (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Patients who have had an examination at the polyclinic will get medicine at the pharmacy, especially outpatients. The pharmacy installation is the last unit that determines the quality of hospital services, so the quality of pharmacy installation services will affect other related units. This study aims to identify value and waste with the Lean Thinking approach in pharmaceutical services, especially during waiting times, the time lag patients receive when submitting a prescription to receiving the prescribed drug. This part has 4 indicators: waiting time for finished drug service ≤ 30 minutes and concoction drugs ≤ 60 minutes, no drug administration errors 100%, customer satisfaction ≥ 80%, and prescription writing according to the formulary 100%. This research used a qualitative approach using the observational action process research method using the lean thinking method to photograph the process flow of outpatient pharmacy services conducted from mid-November to December 2022 in hospital X City of Palopo. The sample was 15 people who would receive the drug and conducted structured in-depth interviews. Data were analyzed using Excel with lean thinking. The study is categorized as lean and proposed improvements to the management support section. Lean thinking can create effective and efficient pharmaceutical governance in improving service quality.